Pengaruh Kesejahteraan Dan Semangat Kerja Terhadap Kinerja Karyawan CV. Gawanta Sejahtera Gemilang Kabupaten Kediri - Febrian Yuga Pratama (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The research aims to know how significant the impact of prosperity and passion for the empoyee effectifity in CV Gawanta Sejahtera Gemilang Kabupaten Kediri. The analysis data in this research uses some test, there are validity test, reability test, classic assumtion test, double linier regency test, partial test (T Test) and simultant test (F test). The taking sample in this research uses saturated sample, and it uses around 32 people to take sample. From analysis, it shows that prosperity of work gives the impact partially and significanly to the work of employee, it can be seen from the value of T about 0,000 ˂0,005. The struggle gives impact partially and significanty to the employee work, it can be known from value of T significant about 0,007˂0.05. The prosperity and spirit of working simultantly dan significantly gives impact to the work of employee of CV. Gawanta Sejahtera Gemilang Kediri, it can be viewed from the value F significant about 0,000 ˂0.05.